Edukasi Optimalisasi Tumbuh Kembang Balita dalam Upaya Pencegahan Stunting - Mila Triana Sari; Melda Amalia (Jurnal Abdimas Kesehatan (JAK), 2020)
AbstractToddler health efforts are activities / work programs in the health sector that concern health services and maintenance for toddlers, namely children aged 12 months to 59 months with the aim of preparing a healthy, intelligent and quality generation while aiming to reduce infant mortality. Based on Lancet data (2012), 44.7% of infant deaths were caused by low birth weight (LBW), failure to breastfeed, Stunting (short), underweight, and lack of vit A and Zink minerals. The MSG program is an effort to prevent the occurrence of stunting by combining several health education methods in one package consisting of conventional health education, distributing leaflets and PMTS as well as training mothers to detect early toddlers at home. This effort is carried out at the basic service level, namely the puskesmas and its working area. The implementation method is divided into 3 stages: the preparation, implementation, monitoring and evaluation stages. Conclusion: all toddlers are in the category of good nutrition, Mothers of toddlers finally know the importance of measuring the growth and development of toddlers, toddlers mothers know the importance of preventing stunting in infancy